Talar Neck Fracture after United Tibiotalar Fusion. (28th September 2015) - Platt, W.; Welck, M.; Rudge, B.
Abstract : Tibiotalar arthrodesis is a well-established treatment for tibiotalar arthritis, for example, in younger high demand patients. Talar neck fractures are less common though well-recognised sequelae of foot ankle trauma. Here we present the clinical case of a 69-year-old male who presented to our institution with a nonunion of a talar neck fracture, having undergone a left tibiotalar fusion 24 years previously. To the authors' knowledge, this injury has only been described once previously in the literature. However, the original case described a fracture sustained in the very early postoperative period following tibiotalar fusion, postulated to be secondary to postimmobilisation osteopaenia or stress risers from metalwork. The aetiology in this case is likely due to axial compression transmitted to the talar neck via the calcaneus. The predisposing factors for nonunion are discussed, highlighting the importance of vigilance for this injury in any patient with concomitant tibiotalar fusion and foot trauma. The management of this patient is discussed.